Keberlanjutan Sistem Usahatani Integrasi Tanaman-Ternak Pasca Bencana Alam Gempa Bumi di Daerah Istimewa Yogyakarta - Hidayat, N. (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2009)
The research was done at the period of August 2001 until September 2002 with location in Jambu, Kepuharjo Village, Cangkringan Sub district, Sleman regency, Daerah Istemewa Yogyakarta province. The purpose of these research to detect the increasing production of Arabica Coffee tree and the economic value from the using faces and urine of dairy cow which have been proceeded being complex organic fertilizer. The research method use “on farm research” with involved farmer groups “Dadi Makmur” that has obtained arabica coffee tree since 1994 and care dairy cow with the property between 3-7 dairy cow/person. In those location has been occur the good integration between the arabica coffee trees with dairy cow livestock. In arabica coffe farm, the farmer use stale waste which in the form of faces and urine that has proceeded being organic fertilizer to fertilize their plantation in order to the producing coffee is called organic coffee. In this research is put complex organic fertilizer to arabica coffee tree in dosages 5kg/tree, 10 kg/tree and as a control is not put fertilizer. The research result indicate that the using fertilizer for 10 kg/tree has very real influence to the amount of unproduce coffee production with increasing product are 46,56 % and give the economic value that is relative bigger when compared with using fertilize 5kg/tree and without fertilize giving (control).   Key words :   Economic value, integration of coffee tree-dairy cow, organic fertilizer